(untitled) (Research, Society and Development, 2022)
Law 12,305/10 which established the National Solid Waste Policy (PNRS) has among its objectives the protection of public health and environmental quality. Therefore, it is important to bring to this discussion the use of social technologies. Thus, this study aimed to evaluate the perception of recyclable material collectors from an association that operates in Campina Grande, state of Paraíba, Brazil on the ergonomics present in the social technologies used in their professional practice. Data collection was performed in five stages with the following themes: Observation of collection technologies, ergonomic analysis and the level of physical effort. Data were analyzed quantitatively and qualitatively, using triangulation. To carry out the collection and transport of solid waste, seven carts were identified, called: C1, C2, C3, C4, C5, C6, C7. For each car, an ergonomics level was linked from the lightest to the heaviest. Car weight, displacement capacity and pain caused at the end of a working day were the most cited problems in the use of these technologies in the professional execution of recyclable material collectors. From what has been observed here, it is necessary to develop new social technologies that generate more quality of life and efficiency in the work of these important professionals.